Themes and recommendations for digitalization of agriculture and agri DPIs - The Agri Collaboratory (CGIAR System Organization, 2025)
The AgX Unconference at Bengaluru, was the second in the global series following Nairobi. It convened diverse stakeholders across India’s agricultural, digital, and policy ecosystem to reflect on the country’s rapid digitalisation journey and its implications for smallholder farmers. Rooted in India’s context and framed through the lived realities of Lakshmi, a representative smallholder farmer navigating uncertainty amid climate variability, market fluctuations, and limited access to advisory and finance, the Unconference surfaced both the challenges and transformative potential of Digital Public Infrastructure (DPI) and Artificial Intelligence (AI) in agriculture.